Fullerene nanowhiskers - Miyazawa, Kun'ichi; Ochiai, Yuichi; Tachibana, Masaru; Kizuka, Tokushi; Nakamura, Shigeo (Singapore : Pan Stanford, 2019)
Fullerenes became a new member of carbon allotropes in addition to diamond and graphite after the discovery of C60 (carbon 60) by Kroto et al. in 1985. The model of C60 was first proposed by Osawa in 1970. C60 is a hollow spherical molecule composed of 60 carbon atoms that contains 12 five-membered rings and 20 six-membered rings and has the same structure as a soccer ball. In 2001, C60 fullerene nanowhiskers (FNWs), which are single-crystal nanowhiskers solely composed of C60 molecules, were discovered in a colloidal solution of lead zirconate titanate (PZT) with added C60. This book focuses on the synthesis of FNWs, fullerene nanotubes, and fullerene nanosheets and describes the structural, mechanical, semiconducting, and thermal properties, as well as bio-related and solar applications of FNWs and related fullerene nanomaterials.
7.3 Assembled C60 Fine Crystals7.4 Conclusion; 8: In situ Transmission Electron Microscopy of Fullerene Nanowhiskers and Related Carbon Nanomaterials; 8.1 Introduction; 8.2 In situ TEM in the Study of Nanomaterials; 8.3 Examples of Measurements; 8.3.1 Elastic Properties of FNWs; 8.3.2 Carbon Nanocapsules; 8.3.2.1 Formation; 8.3.2.2 Luminescence; 8.3.2.3 Conductance; 8.3.2.4 Mechanical properties; 8.3.2.5 In situ TEM of CNCs produced by other methods; 8.4 Conclusions and Outlook; 9: Surface Nanocharacterization of Fullerene Nanowhiskers; 9.1 Introduction
OCLC-licensed vendor bibliographic record.
Keywords: Fullerenes -- Derivatives; Nanotubes; SCIENCE / Chemistry / Inorganic; SCIENCE / Chemistry / General; SCIENCE / Physics; TECHNOLOGY / Material Science